Cultural capital and dietary behavior: A qualitative study in Sargodha city - Nayab Munir (Journal of Professional Research in Social Sciences, 2022)
In the field of human science, social capital includes the social assets of individual (guidance, shrewdness, style of talk, style of dress, etc.) that advance social flexibility in a defined society. Social capital limits as a social-association inside an economy of practices (game plan of exchange), and contains the total of the material and significant items, without capability, that society ponders exceptional and worth pursuing. As a social association inside a game plan of exchange, social capital fuses the accumulated social data that presents monetary prosperity and power. Qualitative research were conducted to investigate the cultural capital and dietary behavior the universe for the present study were the city area of Sargodha. Some are students and some are professionals. Purposive sampling is consider more beneficial for selection of small sample from small geographical areas. The data was collected from 15 participants. The findings of research were according to expectations. People like home made food instead of fast food. Families do not prefer to go outside for eating. People are more conscious to health which is good thing. The date which was collected my some hostelized girls they also prefer traditional food not fast food.